2019
DOI: 10.1029/2019jd030944
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Deep Convective Clouds and Chemistry (DC3) 2012 Studies

Abstract: The Deep Convective Clouds and Chemistry (DC3) project aimed to determine the impact of deep, midlatitude continental convective clouds on tropospheric composition and chemistry. The DC3 field campaign was conducted over a broad area of the central United States during May–June 2012. Data collected by DC3 have been extensively analyzed, with many results published in Deep Convective Clouds and Chemistry 2012 Studies (DC3), a joint special section of JGR Atmospheres and Geophysical Research Letters. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The inclusion of lightning NO x in the free troposphere can substantially contribute to the NO 2 vertical profile and AMF, and thus satellite retrievals (Allen et al, 2021;Pickering et al, 2016;Zhu et al, 2019). Currently, there is a range of an order of magnitude in the lightning NO x emissions reported in the literature (Nault et al, 2017;Schumann & Huntrieser, 2007;Zhu et al, 2019), because of the dependence of lightning NO x on lightning flash rates and potentially other factors like the length of the flash (Pollack et al, 2016) which depend on storm parameters and their uncertainties (Barth et al, 2019). Aircraft measurements along with modeling studies have shown that lightning is the major source of upper tropospheric NO 2 columns over the eastern US (Bertram et al, 2007;Cooper et al, 2006Cooper et al, , 2007Cooper et al, , 2009Lapierre et al, 2020;Nault et al, 2017;Zhu et al, 2019).…”
Section: Lightningmentioning
confidence: 99%
“…The inclusion of lightning NO x in the free troposphere can substantially contribute to the NO 2 vertical profile and AMF, and thus satellite retrievals (Allen et al, 2021;Pickering et al, 2016;Zhu et al, 2019). Currently, there is a range of an order of magnitude in the lightning NO x emissions reported in the literature (Nault et al, 2017;Schumann & Huntrieser, 2007;Zhu et al, 2019), because of the dependence of lightning NO x on lightning flash rates and potentially other factors like the length of the flash (Pollack et al, 2016) which depend on storm parameters and their uncertainties (Barth et al, 2019). Aircraft measurements along with modeling studies have shown that lightning is the major source of upper tropospheric NO 2 columns over the eastern US (Bertram et al, 2007;Cooper et al, 2006Cooper et al, , 2007Cooper et al, , 2009Lapierre et al, 2020;Nault et al, 2017;Zhu et al, 2019).…”
Section: Lightningmentioning
confidence: 99%
“…To obtain these profiles, techniques such as cloud slicing can be used, , but they require a large sample size to reduce noise. Future aircraft observations, like the Deep Convective Clouds and Chemistry (DC3) project, could provide more detailed LNO 2 profiles and improve our understanding of LNO x and air pollution in the Arctic. , …”
Section: Discussionmentioning
confidence: 99%
“…To obtain these profiles, techniques such as cloud slicing can be used, 88,89 but they require a large sample size to reduce noise. Future aircraft observations, like the Deep Convective Clouds and Chemistry (DC3) project, 90 could provide more detailed LNO 2 profiles and improve our understanding of LNO x and air pollution in the Arctic. 75,91 Accurate observations, simulations, and validations of Arctic lightning are crucial for understanding its impact on LNO 2 and other atmospheric processes, as global warming is expected to lead to an increase in its occurrence.…”
Section: ■ Discussionmentioning
confidence: 99%
“…As trace gases remain for more than 1 week in the UT, they are distributed by the upper-level winds around the globe (Ridley et al, 2004). Meanwhile, the vertical profiles of trace gases are reshaped by the updraft and downdraft on timescales of hours (Huntrieser et al, 2016;Barth et al, 2019). On a global scale, the chemical reactions of transported ozone (O 3 ) and its precursors can increase the amount of UT O 3 (Lawrence et al, 2003;Murray, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At present, most aircraft observations and model simulations of convection effects focus on the tropics or the United States (Vaughan et al, 2008;Barth et al, 2019). Little is known about the role of convection in southeastern China (Murray, 2016;Guo et al, 2017), where thunderstorms and lightning have increased significantly because of urbanization during recent decades (Yang and Li, 2014;Pérez-Invernón et al, 2021).…”
Section: Introductionmentioning
confidence: 99%